Cryopreservation of small-volume red blood cells: evaluation of blood group antigen reactivity and its application value - ZHAO Yaling; WANG Yanxia; WANG Ziye; MA Siyu; SHAO Wei; ZHANG Yuanyuan; JIANG Xin; GAN Jia (Zhongguo shuxue zazhi)
[Objective] To establish a cryopreservation protocol for small-volume (≤1 mL) red blood cells (RBCs) and to evaluate the reactivity and stability of blood group antigens after cryopreservation, so as to explore its potential application in immunohematology reference laboratories. [Methods] Small-volume RBCs were cryopreserved for 120 days, followed by thawing and deglycerolization to restore the RBC components. The quality of the RBCs was assessed. Serum antibodies were serially diluted and reacted with RBCs before and after cryopreservation, and agglutination scores were recorded to quantitatively evaluate the reactivity and stability of blood group antigens such as Rh, Duffy, Lewis, Kidd, M, and H. Flow cytometry was used to analyze the percentage and mean fluorescence intensity of ABO antigen expression on RBCs before and after cryopreservation to assess the usability of cryopreserved RBCs in flow immunophenotyping and blood group subtype studies. [Results] The hemolysis rate of thawed and deglycerolized RBCs was (0.27±0.10)%, with a supernatant free hemoglobin level of (0.52±0.14) g/L, and the RBC recovery rate was (69.12±7.91)%. The direct antiglobulin test (DAT) was negative for all thawed RBCs. There was no difference in the reactivity of blood group antigens before and after cryopreservation, and no difference in the percentage and mean fluorescence intensity of A and B antigen expression on RBCs before and after cryopreservation. [Conclusion] The small-volume RBC cryopreservation protocol can be applied to immunohematology analysis in reference laboratories and is expected to be widely used in blood group identification, antibody screening, identification, and blood group-related research.